CFD Analysis on HVAC System Functionality in an Amphitheater - Rahman, M M; Hasan, M M (Journal of Engineering Science, 2024)
Heating, Ventilation and Air conditioning (HVAC) is an important part of residential structures such as single-family homes, apartment buildings, hotels and medium to large industrial and office buildings such as skyscrapers and hospitals, on ships, submarines and in marine environments.This paper investigates the characteristics of the performance HVAC system at “KUET auditorium” regarded as amphitheater for various internal and external conditions. A 2D model of the longitudinal section of the auditorium was drawn by using ANSYS-Fluent software in Design Modeler, for simulating the various functionality of the HVAC system for both summer & winter seasons. In this research, both the indoor & external conditions of KUET auditorium were considered, having the entire spectacle of hall is occupied by people. The main aim of this study was to observe the air temperature, air velocity and relative humidity for each case. The results are represented comparatively as graphs and spectra for various mass flow rates and indoor-outdoor temperatures. It was observed that the HVAC system provided sufficient human comfort conditions in terms of air flow and relative humidty recommended by (American Society of Heating, Refrigerating and Air Conditioing Engineers) AHRAE in the amphitheater for both the summer and winter season. Journal of Engineering Science 14(2), 2023, 01-14